2019
DOI: 10.1109/jeds.2019.2891516
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Graphene-Metal Junction Characterization

Abstract: A reliable method is proposed for measuring specific contact resistivity (ρ C ) for graphenemetal contacts, which is based on a contact end resistance measurement. We investigate the proposed method with simulations and confirm that the sheet resistance under the metal contact (R SK ) plays an important role, as it influences the potential barrier at the graphene-metal junction. Two different complementary metal-oxide-semiconductor-compatible aluminum-based contacts are investigated to demonstrate the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…It has been suggested and demonstrated that the classic TLM may be inappropriate under certain conditions for characterizing G-M contacts. [31][32][33][34][35] Since the sheet resistance of the graphene channel (R SH ) is a dominating component of the total resistance of the device (R T ), and since the TLM technique is based on the comparison of the R T values of the graphene field effect transistors (GFETS) inside the TLM structure, slight changes in R SH along the TLM array will lead to erroneous R C values. In addition, the R SH is different from the sheet resistance of graphene under the metal contact (R SK ) due to the G-M interactions that dope graphene, [27,36,37] and this should be accounted for in the extraction of the parameters describing the G-M junction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested and demonstrated that the classic TLM may be inappropriate under certain conditions for characterizing G-M contacts. [31][32][33][34][35] Since the sheet resistance of the graphene channel (R SH ) is a dominating component of the total resistance of the device (R T ), and since the TLM technique is based on the comparison of the R T values of the graphene field effect transistors (GFETS) inside the TLM structure, slight changes in R SH along the TLM array will lead to erroneous R C values. In addition, the R SH is different from the sheet resistance of graphene under the metal contact (R SK ) due to the G-M interactions that dope graphene, [27,36,37] and this should be accounted for in the extraction of the parameters describing the G-M junction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a broad range of experimental values of 𝑅 𝑐 have been reported in the literature even though the same contact metal has been considered. [83][84][85][86][87][88][89][90][91][92][93] In a metalsemiconductor junction (Schottky contact), a potential barrier (Schottky barrier) is formed at the interface. In an ideal case, the Schottky barrier height is given by the difference between the metal work function and the semiconductor electron affinity (Schottky-Mott approach).…”
Section: Metal-graphene Contact Resistancementioning
confidence: 99%
“…§3.2). Furthermore, parameter extraction techniques based on test-structures or analysis of transport experimental data [81,89,111,112] have been developed towards obtaining an immediate 𝑅 𝑐 value. Further details of these extraction methodologies are provided in §4.2.3.…”
Section: Metal-graphene Contact Resistancementioning
confidence: 99%
“…In general, two transport processes occur in a metal-graphene interface: from the metal contact to the coatedgraphene region and from the coated-graphene region to the uncoated-graphene region [9], [10], [24]. The contact material [10], [21], the contact geometry and dimensions [19], [21], [24] as well as possible additional layers between metal and graphene [8] have an impact on the resistance originated by the first process.…”
Section: Gfet Contact Resistancesmentioning
confidence: 99%
“…In general, two transport processes occur in a metal-graphene interface: from the metal contact to the coatedgraphene region and from the coated-graphene region to the uncoated-graphene region [9], [10], [24]. The contact material [10], [21], the contact geometry and dimensions [19], [21], [24] as well as possible additional layers between metal and graphene [8] have an impact on the resistance originated by the first process. A bias-dependent potential barrier induced by a difference in the electronic properties of the coated and the uncoated graphene portions [9], [10] is the main cause of the resistance associated to the second process.…”
Section: Gfet Contact Resistancesmentioning
confidence: 99%